Molecularly Imprinted Polymer Waveguides for Direct Optical Detection of Low‐Molecular‐Weight Analytes. Issue 23 (25th September 2014) - Sharma, Nityanand; Petri, Christian; Jonas, Ulrich; Bach, Monika; Tovar, Günter; Mrkvová, Kateřina; Vala, Milan; Homola, Jiří; Knoll, Wolfgang; Dostálek, Jakub
<x xml:space="preserve">Abstract</x> New composite layer architecture of 3D hydrogel polymer network that is loaded with molecularly imprinted polymer nanoparticles (nanoMIP) is reported for direct optical detection of low‐molecular‐weight compounds. This composite layer is attached to the metallic surface of a surface plasmon resonance (SPR) sensor in order to simultaneously serve as an optical waveguide and large capacity binding‐matrix for imprinted target analyte. Optical waveguide spectroscopy (OWS) is used as a label‐free readout method allowing direct measurement of refractive index changes that are associated with molecular binding events inside the matrix. This approach is implemented by using a photo‐crosslinkable poly(N‐isopropylacrylamide)‐based hydrogel and poly[(ethylene glycol dimethylacrylate)‐(methacrylic acid)] nanoparticles that are imprinted with l‐Boc‐phenylalanine‐anilide (l‐BFA, molecular weight 353 g mol−1). Titration experiments with the specific target and other structurally similar reference compounds show good specificity and limit of detection for target l‐BFA as low as 2 × 10−6m. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>